Indian treaties, Canada - Canada. Department of Mines and Technical Surveys (Cartographer)
Shows Indigenous treaties across Canada. Material digitized as part of an Academic Innovation Fund (AIF), awarded in 2018. For more information see: http://avptl.info.yorku.ca/academic-innovation-fund/ . Scale 1:8,870,440, or 140 miles to 1 inch. Lambert comformal conical projection. Map outlining a number of treaties between Indigenous peoples and the Canadian government.